Texts in Context: Scripture and the Divine Economy - Rae, Murray (Journal of theological interpretation, 2007)
In this article I investigate the phenomenon of hermeneutical plurality with respect to biblical texts. My purpose is to defend the legitimacy of claims that a scriptural text may speak in ways that diverge from the "original meaning" of a text, so far as that may be discerned, but also to offer a theological account of the limits that must be set upon this hermeneutical freedom. I begin by locating my argument within the landscape of recent hermeneutical debates, go on to explore, as a case study, the text of Isa 52:13–53:12, and then develop a theological account of what is involved in speaking of the "meaning" of a biblical text.